Genome Sequence of Kosakonia radicincitans Strain YD4, a Plant Growth-Promoting Rhizobacterium Isolated from Yerba Mate (Ilex paraguariensis St. Hill.) - Bergottini, Veronica M; Filippidou, Sevasti; Junier, Thomas; Johnson, Shannon; Chain, Patrick S; Otegui, Monica B; Zapata, Pedro D; Junier, Pilar (My University, 2015)
Kosakonia radicincitans strain YD4 is a rhizospheric isolate from yerba mate (Ilex paraguariensis St. Hill.) with plant growth-promoting effects on this crop. Genes involved in different plant growth-promoting activities are present in this genome, suggesting its potential as a bioinoculant for yerba mate.